under Increased Hydrogen Peroxide conditions, the Antioxidant Effects of Pequi oil (Caryocar brasiliense camb.) to decrease dnA damage in runners are Influenced by Sex, Age and oxidative Stress-related Genetic Polymorphisms - Miranda-Vilela, Ana Luisa; Alves, Penha Cristina Zaidan; Akimoto, Arthur Kenji; Lordelo, Graciana Souza; Klautau-Guimarães, Maria de Nazaré; Grisolia, Cesar Koppe (Free Radicals and Antioxidants)
Context: Exhausting exercise, increasing reactive oxygen species, can overwhelm the endogenous antioxidant system’s capacity, resulting in oxidative damage to DNA. Deficient antioxidant defenses, influenced by certain genetic polymorphisms, may contribute. Aims: We aimed to investigate whether carotenoid-rich oil from pequi (Caryocar brasiliense) could decrease DNA damage in athletes submitted to increased hydrogen peroxide (H2O2) conditions and in those less genetically favored by antioxidant defenses. Methods and Material: Runners’ blood (N = 125) was analyzed after races under the same environment, type, intensity and length of weekly training conditions, before and after 14 days of pequi-oil supplementation. DNA damage was assessed by comet assay before and after H2O2 exposure, with gene polymorphisms of MnSOD Val9Ala, CAT –21A/T, GPx-1 Pro198Leu, delGSTM1, delGSTT1, ACE and Haptoglobin. Results: Without additional oxidative stress imposed by H2O2, pequi oil was particularly efficient reducing DNA damage for women, age group of 20-40 years, distance of 8-10 Km and genotypes MnSOD Val/Ala, CAT TT, GPx-1 Pro/Leu, GSTM1 null, GSTT1 non-null, ACE DD and II and Hp1F-2. For treatment with H2O2 at 0.25 mM, pequi oil resulted in decreased DNA damage only for running 16-21 Km; for treatment with 1 mM, decrease was for 20-40 years and genotypes GPx-1 Pro/Pro and ACE ID. Conclusions: Pequi oil’s effect on exercise-induced DNA damage was therefore influenced by sex, age and genetic polymorphisms, indicating that: long-distance races can be harmful, mainly for older athletes, due to oxidative stress above organism adaptability; genotypes showed different responses; under increased H2O2 conditions, GPx-1 Pro/Pro and ACE ID genotypes were more responsive to antioxidant supplementation.
Keywords: reactive oxygen species; hydrogen peroxide; exercise-induced oxidative stress; exercise-induced DNA damage; comet assay; gene polymorphisms related to oxidative stress